Exceptional longevity does not result in excessive levels of disability - Christensen, Kaare; McGue, Matt; Petersen, Inge; Jeune, Bernard; Vaupel, James W (Proceedings of the National Academy of Sciences - PNAS, 2008)
Late-life loss of independence in daily living is a central concern for the aging individual and for society. The implications of increased survival to advanced age may be different at the population level than at the individual level. Here we used a longitudinal multi-assessment survey of the entire Danish 1905 cohort from 1998 to 2005 to assess the loss of physical and cognitive independence in the age range of 92 to 100 years. Multiple functional outcomes were studied, including independence, which was defined as being able to perform basic activities of daily living without assistance from other persons and having a MiniMental State Examination (MMSE) score of 23 or higher. In the aggregate, the 1905 cohort had only a modest decline in the proportion of independent individuals at the 4 assessments between age 92 and 100 years: 39%, 36%, 32%, and 33%, with a difference between first and last assessment of 6% [95% confidence interval (CI), -1-14%]. For participants who survived until 2005, however, the prevalence of independence was reduced by more than a factor of 2, from 70% in 1998 to 33% in 2005 (difference, 37%; 95% CI, 28-46%). Similar results were obtained for the other functional outcomes. Analyses of missing data resulting from nonresponse and death suggest that the discrepancy between the population trajectory and the individual trajectory is caused by increased mortality among dependent individuals. For the individual, long life brings an increasing risk of loss of independence. For society, mortality reductions are not expected to result in exceptional levels of disability in cohorts of the very old.